2014
DOI: 10.1097/01.ogx.0000455024.52578.2f
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Detriment of Venous Thromboembolism With Epithelial Ovarian Cancer

Abstract: More than 10% of cancer patients have venous thromboembolism (VTE). There is a clear relationship between VTE and several types of solid tumors; VTE negatively impacts survival. This disorder is the second leading cause of death in cancer patients. Some studies have reported that the solid tumor with the highest rate of VTE is ovarian cancer. Few studies have evaluated the contribution of VTE timing to survival in patients with solid tumors. A substantial proportion of deaths in cancer patients may be preventa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…53 Indeed, later studies showed that VTE is frequent in ovarian cancer patients 12,13,25 and correlates with reduced survival rates. 54,55 Accumulating experimental evidence suggests that the histological type of EOC with the highest incidence of VTE is CCC. [24][25][26][27][56][57][58] It is conceivable that TF plays a major role in VTE in ovarian cancer patients, given that TF can be highly expressed in EOC tissues.…”
Section: Relationship Between Vte and Tf-f Viia Complex Activity In Omentioning
confidence: 99%
“…53 Indeed, later studies showed that VTE is frequent in ovarian cancer patients 12,13,25 and correlates with reduced survival rates. 54,55 Accumulating experimental evidence suggests that the histological type of EOC with the highest incidence of VTE is CCC. [24][25][26][27][56][57][58] It is conceivable that TF plays a major role in VTE in ovarian cancer patients, given that TF can be highly expressed in EOC tissues.…”
Section: Relationship Between Vte and Tf-f Viia Complex Activity In Omentioning
confidence: 99%
“…The development of VTE has a negative impact on overall survival with PE being the leading cause of death in ovarian malignancy. 28,29 The type and timing of therapeutic anticoagulation has to be balanced against the perioperative bleeding risk and the risk of further VTE. Two retrospective case series have shown reduced rates of PE with the use of IVCFs preoperatively in gynaecological and other malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…VTE negatively impacts survival, which may indicate that thrombotic signaling promotes a more aggressive tumor behavior. 9,16 Risk factors for VTE in ovarian cancer are advanced stage (III, IV), clear cell histology, chemotherapy, extensive cyto-reductive surgery, high-grade serous adenocarcinoma. 10 Patients with VTE during primary treatment for ovarian cancer (clear cell) had a 3.9-fold increase in risk of recurrence and a 6.3-fold increase in risk of death, and VTE remained an independent prognostic factor for death, even after controlling the disease.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 VTE disease (pulmonary embolism [PE] and deep vein thrombosis [DVT]) are significantly associated with ovarian cancer 7 and adversely impact patient survival. [7][8][9][10] This case report outlines the discovery of occult ovarian cancer in a patient who exhibited acute cerebrovascular events with an incidental detection of patent foramen ovale (PFO).…”
mentioning
confidence: 99%